Comparison of hemp and cotton fiber implants in muscle rat tissue. Study of the inflammatory response - Dorfman, Saúl; Dorfman, Denny; Leonardi, Régulo; Maroso, Juan; Cardozo, José; Durán, Alvaro (Investigación Clínica, 2013)
Â Hemp fiber 1s obtained from the plant Musa textilis. The cost of preparation of its raw fibers 1s low. The purpose of this paper was to compare the inflammatory response in the rat muscle tissue originated by both hemp and cotton fibers. Both types of fibers, were implanted in gluteal muscles of Sprague Dawley rats. The rats were sacrificed at 15, 30 and 60 postoperatíve days. Muscle tissue sections were stained with hematoxilyneosin. The inflammatory response was measured by subtracting the suture surface area from the total granulomatous area. At 15 days, the inflammatory response was more conspicuous for hemp than for cotton fiber (P<0.05). At 30 and 60 days, responses were similar (P> 0.05). We cannot conclude that the hemp fiber is superior to cotton, nevertheless, they behave the same. Therefore, hemp constitutes an alternative as suture material.